Existence and its Levels from Aziz Nasafi Viewpoint - Ehsan Reisi (ادبیات عرفانی, 2013)
After the profound transformation which emerged in the Islamic mysticism in the seventh century Hegira, ontology was added to the other two pillars of mystical cognition, theology and anthropology. Accordingly, in the second tradition of mysticism understanding the existence is not only a theoretical knowledge but also is achieved by accessing the perfection levels and the cognition of God results from the cognition of human self and existence. The linkage between anthropology and ontology for cognition acquisition opened new horizons to the mystics of the second tradition. Consequently, with the coupling of human and existence positions, as microcosm and macrocosm, new aspects of these two worlds were recognized. Aziz Nasafi, who is one of the innovative mystics of the second tradition in mysticism, introduces new plans for mystical ontology which are compatible in general principles with the other ontological plans of the second tradition, but are unique in details. This article investigates and analyzes his views on existence and its various levels.